1985
DOI: 10.1042/bj2280061
|View full text |Cite
|
Sign up to set email alerts
|

Proton-n.m.r. study of interaction of myelin basic protein with a monoclonal antibody

Abstract: Proton n.m.r. at 400 MHz has been applied to study the interactions of bovine or porcine myelin basic protein (b- or p-MBP) with a monoclonal antibody to human (h-) MBP. The antibody, an IgG immunoglobulin that contains a sequential epitopic region, cross-reacts with b-MBP but not with p-MBP, the presumed epitope being identical in h- and b-MBP. N.m.r. spectra were recorded from the Fab fragment of the antibody and for mixtures of Fab and MBP at various molar ratios. The n.m.r. spectrum of MBP in the mixture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the segment comprising residues 120-140, A-133 and S-137 in r-MBP are substituted by proline residues in p-MBP. Variations in the conformation of this region of MBP from different species were established in NMR studies of the interactions of the protein with a monoclonal antibody to an epitope consisting of the linear sequence of residues 130-139 of bovine MBP (Mendz et al, 1985). The fact that some resonances of peptide 99-179 " Segments predicted to be capable of forming amphipathic helices are shown.…”
Section: Resultsmentioning
confidence: 99%
“…In the segment comprising residues 120-140, A-133 and S-137 in r-MBP are substituted by proline residues in p-MBP. Variations in the conformation of this region of MBP from different species were established in NMR studies of the interactions of the protein with a monoclonal antibody to an epitope consisting of the linear sequence of residues 130-139 of bovine MBP (Mendz et al, 1985). The fact that some resonances of peptide 99-179 " Segments predicted to be capable of forming amphipathic helices are shown.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the 1 H resonances of the RSF aqueous solution prior to gelation have been assigned by closely examining the expanded 1 H NMR spectra (Fig. 2a-f) and matching their values with the values of all amino acid residues available in the literature [60][61][62][63][64][65][66], as summarized in Table 1. Taking into account that both fresh and aged silk solution strongly demonstrated the presence of mixed conformations, so the 1 H resonances were determined as an average of all resonances emerged from random coil, a-helix and b-strand.…”
Section: H Nmr Analysismentioning
confidence: 99%
“…The conformation of the octapeptide, as revealed by this n.m.r. study in aqueous solution, may be compared with the interaction of the epitopic region of MBP with the monoclonal antibody (Mendz et al, 1985). The position of the tyrosine residue is consistent with its important role in binding to the receptor site.…”
Section: Residuementioning
confidence: 85%
“…A 'H n.m.r. study of the interaction of b-MBP with one of the monoclonal antibodies showed a strong effect at the tyrosine residue (Tyr-1 35) in the basic protein, but no effect at the histidine residue (His-139) (Mendz et al, 1985). A preliminary n.m.r.…”
mentioning
confidence: 95%